Effect Of Dragon Fruit Dadih Fortified With Selenium on SREBP-1c Expression and Liver Histopathology in Obese Rats - Safitri, Ulan; Rustanti, Ninik; Pramono, Adriyan (Scripta Medica, 2025)
Background/Aim: Obesity remains a major global health challenge, closely linked to an increased likelihood of developing metabolic disorders, such as non-alcoholic fatty liver disease (NAFLD), insulin resistance, type 2 diabetes and cardiovascular complications. This study aimed to investigate the effect of selenium-fortified dragon fruit dadih on sterol regulatory element-binding protein-1c (SREBP-1c) expression and liver histopathology in obese rats induced by a high-fat, high-fructose diet (HFFD). Methods: Dadih, a traditional Indonesian fermented dairy product, was enriched with selenium (0.4 ppm) and 10 % red dragon fruit juice to enhance its antioxidant and metabolic regulatory properties. Thirty-six male Sprague-Dawley rats were divided into four groups: healthy control (K−), obesity control (K+), dadih (Di) and selenium-fortified dragon fruit dadih (Di+). After 28 days of intervention, liver tissues were analysed for SREBP-1c expression and histopathological alterations. Results: The results showed a significant increase in hepatic SREBP-1c expression in the obese control group (2172.8 ± 32.3 pg/mL) compared to the healthy control (999.2 ± 45.5 pg/mL; p < 0.001). Intervention with Di reduced SREBP-1c expression to 1455.2 ± 40.3 pg/mL. At the same time, the Di+ group showed a greater reduction to 1174.0 ± 58.8 pg/mL (p < 0.001), suggesting a more potent suppression of hepatic lipogenesis with selenium and dragon fruit enrichment. Histopathological analysis revealed hepatocyte ballooning and inflammatory cell infiltration in the obese control group, indicating early signs of liver injury. Although steatosis was not yet prominent due to the relatively short 28-day induction period, structural alterations in hepatocytes were already evident and likely associated with elevated SREBP-1c expression. These pathological changes were attenuated in the intervention groups, especially in Di+, which showed more pronounced improvements in liver architecture. Conclusion: Selenium-fortified dragon fruit dadih holds promise as a functional dietary intervention to attenuate hepatic lipogenesis and protect against obesity-induced liver damage by downregulating SREBP-1c. Further studies are warranted to evaluate its long-term effects and underlying molecular mechanisms.
Keywords: Obesity; Selenium-fortified dadih; Sterol regulatory element binding protein 1; Dairy products; Non-alcoholic fatty liver disease; Metabolism; Health